A deep insight into the structure and performance evolution of aramid nanofiber films induced by UV irradiation. (September 2019) - Luo, Jingjing; Zhang, Meiyun; Nie, Jingyi; Liu, Guodong; Tan, Jiaojun; Yang, Bin; Song, Shunxi; Zhao, Joe R.
Abstract: Aramid nanofibers (ANFs) have been extensively explored in various fields since their emergence as high-performance nanoscale building blocks. ANF films exhibit strong sensitivity to ultraviolet (UV) irradiation which could deteriorate their performances. However, the sensitivity to UV irradiation has not been sufficiently understood yet. In this paper, for the first time, the surface structure and performance evolution of UV-irradiated ANF films are evaluated systematically. Results demonstrate that the fibrous nanofibers on the ANF films surface have been ultimately degraded into powdery nanoparticles, resulting from the chain scission, and the oxidation of amides groups in the ANFs. Moreover, newly formed anhydride has also been detected, which is derived from the chemical crosslinking of the oxidation products of the ANFs. Due to such structural evolution, some parameters of the ANF films display a downward trend within 72 h, and then a rising trend in the next 96 h. These parameters include the surface roughness, mechanical properties, water contact angles and temperature of weight loss at 10% (TG10% ) of ANF films, while the crystallinity and temperature of maximum derivative weight curve (Tmax ) present opposite results. Highlights: Structure and performance evolution of UV-irradiated ANF films are first investigated. The fibrous nanofibers on ANF film surface degrade into powdery nanoparticles. Oxidative degradation and chemical crosslinking are both detected.